FAKTOR DEMOGRAFI DALAM STRATEGI ELEKTORAL PILKADA: PERSPEKTIF DARI LAPANGAN - Kuskrido Ambardi (Populasi, 2016)
Demographic analysis is an important part of electoral strategies. This paper will show that electoral candidates in Indonesian local elections intituitively make use of demographic mapping for formulating their electoral strategies to win the elections. However, they purposefully and selectively target only a set of particular demographic groups that provide them electoral gains while ignoring others. Religious, ethnic, and migrant divisions are seen as more important electorally than gender and rural-urban divisions. To mobilize these groups, they tend to develop non-policy-based or symbolic campaigns instead of formulating policy-based campaigns. As a result, in local elections, primordial issues are more prominent than policy issues. In the short run, demographic analysisis will stay as the main strategic electoral tool for these candidates. In the long run, however, this mode of analysis will have to compete against post-demographic modes of analysis that have started to gain traction among national and local politicians.